ETMR-13. NFI GENES IN ETMR TUMORIGENESIS AND NEURODEVELOPMENT. (4th December 2020) - Bunt, Jens; Lambo, Sander; Lim, Jonathan; Mauermann, Monika; Pfister, Stefan; Richards, Linda; Kool, Marcel
Abstract: Embryonal tumors with multilayered rosettes (ETMRs) are aggressive pediatric embryonal brain tumors with a universally poor prognosis. These tumors are commonly characterized by amplification of C19MC, but other miRNA-related aberrations, such as DICER mutations or MIR17HG amplifications, are also observed. Nevertheless, it remains unknown how these aberrations are driving the tumorigenesis. We applied miRNA target prediction to investigate the downstream targets shared by these aberrations affecting normal brain development and tumorigenesis. The nuclear factor one ( NFI ) family of transcription factors were found to be top candidates shared by both miRNA clusters. These genes are expressed at very low levels in ETMRs, in contrast to other brain tumors. During normal brain development these genes are expressed in radial glial progenitors and are required for the transition of proliferation to differentiation. Since radial glial progenitors are the potential cell-of-origin of ETMRs, we hypothesize that downregulation of NFI is required for the proliferative, undifferentiated state of ETMRs. Indeed, mouse models with deletion of an Nfi family member display sustained proliferation and delayed differentiation of radial glial progenitors during development. This leads into brain overgrowth, which has also been observed in humans with intellectual disabilities caused by NFI haploinsufficiency. When multiple Nfi family members are simultaneously targeted in mice, the progenitors are retained and both neurogenesis and gliogenesis are inhibited, resulting in a neuropathology similar to that of human ETMR tumors. Hence, downregulation of NFI genes resulting from miRNA aberrations could contribute to the developmental state and possibly tumorigenesis of ETMRs.